2012
DOI: 10.3390/jfb3040776
|View full text |Cite
|
Sign up to set email alerts
|

Mineralization Content Alters Osteogenic Responses of Bone Marrow Stromal Cells on Hydroxyapatite/Polycaprolactone Composite Nanofiber Scaffolds

Abstract: Synthetic tissue scaffolds have a high potential impact for patients experiencing osteogenesis imperfecta. Using electrospinning, tissue scaffolds composed of hydroxyapatite/polycaprolactone (HAp/PCL) composite nanofibers were fabricated with two different HAp concentrations—1% and 10% of the solid scaffold weight. After physico-chemical scaffold characterization, rat bone marrow stromal cells were cultured on the composite scaffolds in maintenance medium and then in osteogenic medium. Quantitative PCR, colori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 91 publications
(110 reference statements)
2
11
0
Order By: Relevance
“…For example, one should expect the osteogenic differentiation in rigid mineral-containing scaffolds, the neural differentiation in soft hydrogel systems, and the angiogenic differentiation in fibrin-based hydrogels. 141 144 …”
Section: Pbm For Tissue Engineering and Regenerative Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…For example, one should expect the osteogenic differentiation in rigid mineral-containing scaffolds, the neural differentiation in soft hydrogel systems, and the angiogenic differentiation in fibrin-based hydrogels. 141 144 …”
Section: Pbm For Tissue Engineering and Regenerative Medicinementioning
confidence: 99%
“…For example, one should expect the osteogenic differentiation in rigid mineral-containing scaffolds, the neural differentiation in soft hydrogel systems, and the angiogenic differentiation in fibrin-based hydrogels. [141][142][143][144] One of interesting PBM effects, which can be of great practical importance, is its protective ability. It was reported in neurotraumas and neonatal hypoxia-ischemia.…”
Section: Pbm For Tissue Engineering and Regenerative Medicinementioning
confidence: 99%
“…In this study, it was observed that the PCL/PCL-g-HAp nano-composite scaffold improved the cells proliferation and cell-cell connections until the end of day 21 of culture as according to MTT assay results as well as cell morphology studies (Figure 9). A remarkable increase in integrin binding sites is prerequisite for such event [31]. Integrin transmembrane proteins act similar to other protein receptors (proteins that play a role in cell-cell signaling and at the meanwhile integrins are known as focal points of the cell cytoskeleton.…”
Section: Insert Figurementioning
confidence: 99%
“…The significant number of works published on the subject in the past few years and also the increase in published patents [7] reflect the above-mentioned interest, as well as the variety of purposes for this technology. Applications for ENf are as wide as tissue engineering and biomedical devices [8,9], oral drug delivery [10], functional materials (e.g. nano-sensors and fuel cells) [6,11] enzyme (protein) surface immobilization or nanoencapsulation [12].…”
Section: Introductionmentioning
confidence: 99%